A Frame-Based Conjugate Gradients Direct Search Method with Radial Basis Function Interpolation Model - Xiaowei Fang; Qin Ni (Discrete Dynamics in Nature and Society)
In this paper, we propose a new hybrid direct search method where a frame-based PRP conjugate gradients direct search algorithm is combined with radial basis function interpolation model. In addition, the rotational minimal positive basis is used to reduce the computation work at each iteration. Numerical results for solving the CUTEr test problems show that the proposed method is promising.